2005
DOI: 10.2176/nmc.45.627
|View full text |Cite
|
Sign up to set email alerts
|

Acute Subdural Hematoma After Intro-arterial Thrombolysis for Acute Ischemic Stroke-Case Report-

Abstract: A 79-year-old man with a cardiac pacemaker for bradycardia fell down and presented with sudden onset of right hemiplegia and aphasia. Initial computed tomography (CT) showed no cerebral infarction but angiography revealed occlusion of the left middle cerebral artery (MCA). Local intra-arterial thrombolysis with tissue plasminogen activator (tPA; tisokinase, 1,600,000 units) was performed 3 hours after the onset, and the MCA was partially recanalized. Further administration of tPA was suspended because of noseb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Clinical studies PROACT 8 and PROACT II 9 reported a high recanalization rate in intra-arterial thrombolysis (IAT) and a good outcome in ischemic cerebrovascular disease. However, the high recanalization rate was associated with intracranial hemorrhage which is the most worrying problem due to the increased mortality [9][10][11] . Urokinase was commonly used in thrombolytic treatment in developing countries because of the low price and good pharmacodynamic action.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies PROACT 8 and PROACT II 9 reported a high recanalization rate in intra-arterial thrombolysis (IAT) and a good outcome in ischemic cerebrovascular disease. However, the high recanalization rate was associated with intracranial hemorrhage which is the most worrying problem due to the increased mortality [9][10][11] . Urokinase was commonly used in thrombolytic treatment in developing countries because of the low price and good pharmacodynamic action.…”
Section: Introductionmentioning
confidence: 99%
“…However, their brain NCCT showed no evidence of bleeding. ICH has been describe when AIS patients with head trauma are treated with rtPA 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Timely recanalization of the target vessel in an acute ischemic stroke is associated with a 4- to 5-fold increase in the odds of a good clinical functional outcome and a 4- to 5-fold reduction in the odds of death [4]. Although endovascular therapy is a useful treatment option, the presence of a bleeding risk, such as intracranial hemorrhage or abnormal hemostasis, has been an exclusion criterion in decision-making regarding the use of chemical thrombolytics [2, 5]. However, the use of MT alone in patients at risk of bleeding may seem feasible and safe.…”
Section: Discussionmentioning
confidence: 99%